Implementation of The Just-In-Time Method on Drug Inventory Efficiency at The Pharmacy Department of Kaliwates Hospital Jember - Adityo Herjuno; Afifah Machlaurin; Yuni Retnaningtyas; Abu Khoiri; Wilda Zidni Ilma (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2026)
Background: During the Covid-19 pandemic, the management of drug inventory and sypply faces a great challenges. A common problem in the management of supplies at the pharmacy installation is the accumulation of drugs that are rarely used, which causes drugs to become damaged or expired, as well as the shortage of drugs that should be available. RSU Kaliwates Jember has implemented a strategy in 2023 to optimize the drug inventory in the Pharmacy department by applying a Just-In-Time strategy in drug purchasing. This study aims to analyze the impact of the strategy in three sector: drug procurement cost, total inventory cost, and inventory day. Methods: The analysis applied the Quacy-experimental one group pretest-posttest design. The main goal is to analyze causal relationships by comparing the results of the two tests in order to determine the impact of the treatment. This study is a one-group pretest-posttest research design by comparing the value before and after the implementation of just-In-Time strategy, value at 2022 and 2023. The data was obtained from system management at RSU Kaliwates Jember (SIMRS) for procurement cost, inventory values, an inventory days. Results: The analysis showed that there is a significant efficiency in drug procurement cost with a p-value of 0.041. For the total inventory value, the strategy could significantly reduce the value wiyh p-value of 0.006. In addition, the strategy could shorten significantly the inventory days with p-value 0.017. Conclusions: This study conclude that the implementation of just-in-time strategy has an impact on improving the efficiency of drug inventory management especially in the reduction of the procurement cost, inventory value and inventory days. The impact of this strategy is worth to further analyze in the other sector such us in the drug wastage due to dead stock or expire drug and drug shortage that could affect the pharmacy care.